A JOINT ECONOMIC LOT SIZING MODEL FOR SUPPLIER-MANUFACTURER UNDER PROBABILISTIC DEMAND AND PROBABILISTIC LEAD TIME - EKAWATI (NIM: 23408068), IRNA
This research introduces a joint economic lot sizing model for a supplier and a manufacturer under probabilistic demand and probabilistic lead time. A mathematical model is formulated with assuming single supplier, single manufacturer, demand and lead time follows normal distribution. Decision variables for this model are ordering lot size's manufacturer, reorder point level's manufacturer and production lot size's supplier. The optimal decision variables are obtained by minimizing the total expected cost function for the supplier and the manufacturer. A searching method is used to find the optimal solution as the objective function involves three variables and it is not possible to obtained the optimal solution analytically. The optimal solution is obtained by developing an algorithm that modifies the Hadley and Within algorithm.